Analisis Keputusan Transfer Pricing Berdasarkan Pajak, Tunneling dan Exchange Rate - Hani Sri Mulyani; Endah Prihartini; Dadang Sudirno (ITB AAS INDONESIA, 2020)
Tax has two points of view, for the government tax is a source of state revenue that has the largest contribution, but for tax companies is a burden that must be paid. Often companies do tax planning strategies so that the tax burden that must be borne by the company becomes smaller. Companies usually exploit loopholes from the use of accounting methods allowed by accounting and taxation rules. Transfer Pricing is one of the ways companies take to reduce the tax burden. This study aims to determine and obtain empirical evidence about the effect of tax, tunneling and exchange rates on transfer pricing decisions both partially and simultaneously on manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2013-2017 period. The research method used is descriptive and verification analysis method. The population in this study were 144 manufacturing companies listed on the Indonesia Stock Exchange in the period 2013-2017. Sampling using a purposive sampling method and obtained a sample of 20 companies. The results of this study indicate that partially significant positive effect on transfer pricing decisions, tunneling does not significantly influence the transfer pricing and exchange rate decisions do not significantly influence the transfer pricing decision, but simultaneously the results of this study indicate that taxes, tunneling and exchange rates affect significant to the transfer pricing decision.